2003
DOI: 10.1046/j.1462-2920.2003.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and phylogenetic characterization of bacteria capable of inducing differentiation in the green alga Monostroma oxyspermum

Abstract: Many green algae cannot develop normally when they are grown under axenic conditions. Monostroma oxyspermum, for example, proliferates unicellularly in an aseptic culture, but develops into a normal foliaceous gametophyte in the presence of some marine bacteria. More than 1000 bacterial strains were isolated from marine algae and sponges and assayed for their ability to induce the morphogenesis of unicellular M. oxyspermum. Fifty bacterial strains exhibiting morphogenesis-inducing activity against unicellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 46 publications
5
110
0
1
Order By: Relevance
“…The aberrant morphology was successfully reversed to the foliose thallus following the inoculation of appropriate morphogenesisinducing bacterial isolates to the culture media (Nakanishi et al 1996). Similar findings have been reported in studies with Ulva pertusa (Nakanishi et al 1996), U. linza (Marshall et al 2006), U. mutabilis (Wichard & Oertel 2010), Enteromorpha linza (Fries 1975), E. compressa (Fries & Aberg 1978), and Monostroma oxyspermum (Tatewaki et al 1983, Matsuo et al 2003. Direct physical contact between the algal and bacterial cells was shown to be a prerequisite for complete morphogenesis in U. pertusa (Nakanishi et al 1999).…”
Section: Ulva Fasciatasupporting
confidence: 79%
See 1 more Smart Citation
“…The aberrant morphology was successfully reversed to the foliose thallus following the inoculation of appropriate morphogenesisinducing bacterial isolates to the culture media (Nakanishi et al 1996). Similar findings have been reported in studies with Ulva pertusa (Nakanishi et al 1996), U. linza (Marshall et al 2006), U. mutabilis (Wichard & Oertel 2010), Enteromorpha linza (Fries 1975), E. compressa (Fries & Aberg 1978), and Monostroma oxyspermum (Tatewaki et al 1983, Matsuo et al 2003. Direct physical contact between the algal and bacterial cells was shown to be a prerequisite for complete morphogenesis in U. pertusa (Nakanishi et al 1999).…”
Section: Ulva Fasciatasupporting
confidence: 79%
“…However, very few studies were performed with isolates of bacteria that were phylogenetically well characterized. In the present study, isolates were identified by partial 16S rRNA gene sequences, and phylogenetic analysis showed that all 5 putative bacterial isolates were morphogenesisinducing bacterial isolates (Matsuo et al 2003). Only 5 out of 53 bacterial isolates showed statistically significant induction of U. fasciata growth, morphology, and zoospore induction.…”
Section: Discussionmentioning
confidence: 62%
“…By using CARD-FISH analysis we found that bacteria accounted for more than 90% of the cells in the microbial community over all four seasons. This is relatively high in comparison to the average of 56% determined in a review of FISH studies in aquatic environments (Bouvier and del Giorgio, 2003) and could be a reflection of the importance of bacteria for the normal morphological growth of Ulva (Provasoli and Pintner, 1980;Nakanishi et al, 1996;Matsuo et al, 2003). The larger non-hybridized cells observed frequently on the surface of U. australis are possibly diatoms and microalgae, which is in agreement with scanning electron micrographs-based observations of microfouling of small diatoms and blue-green algae on seaweed surfaces (Sieburth, 1975;Provasoli and Pintner, 1980;Dobretsov and Qian, 2002).…”
Section: ) and Coralsmentioning
confidence: 72%
“…As Bacteroidetes bacteria have been found to contribute 15-30% of the DMSP assimilation in the North Atlantic Ocean and the Gulf of Mexcio (Malmstrom et al, 2004), it is possible that the relatively high abundance of this group may also be linked to DMSP production by the alga. Bacteroidetes bacteria have also been linked with the maintenance of normal thallus structure in the green alga Monostroma oxyspermum (Matsuo et al, 2003), although bacteria from a range of phyla including the Proteobacteria have also been shown to induce normal morphology in the green alga Ulva linza (Marshall et al, 2006). Six of the seven Bacteroidetes sequences are closely related to the Saprospiraceae family, strains of which have been isolated from seawater (Lee, 2007;Oh et al, 2009) and algae (Hosoya et al, 2006).…”
Section: ) and Coralsmentioning
confidence: 99%
“…The closest cultured relatives to L7B9 348 and L7B14 were Tenacibaculum amylolyticum (90% sequence identity) (Suzuki et al 349 2001) and Cytophaga sp. MBIC04693 (94% sequence identity) (Matsuo et al 2003), 350 which are both algae-associated bacteria. 351…”
mentioning
confidence: 99%